2017
DOI: 10.1093/jee/tox182
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maize Hybrid on Biology and Life Table Parameters of the Trogoderma granarium (Coleoptera: Dermestidae)

Abstract: The khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae), is a polyphagous pest that infests many stored grains and products. The effect of nine maize hybrids including 704, AR 89, AS 71, AS 77, BC 678, KSC 703, PL 472, SC 704, and Simax was studied on biology and life table parameters of T. granarium at controlled conditions (33 ± 1 °C, 65 ± 5% RH, and a photoperiod of 14:10 [L:D] h). According to the results of this study, the immature period was the longest on BC 678 (56.79 ± SE: 1.51 d) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…When rearing an insect species, there is a relationship between the quality and quantity of food offered and their larval growth rate ( Grandison et al 2009 , Borzoui et al 2018 , Suits et al 2017 ). Moreover, larval diet has a considerable impact on adult fecundity and egg fertility ( Zhang et al 2011 , Majd-Marani et al 2017 ). Eating a low-quality food has been associated with high mortality, reduced growth, delayed development, and low reproductive output in insect herbivores ( Awmack and Leather 2002 , Behmer 2006 , Suits et al 2017 ).…”
mentioning
confidence: 99%
“…When rearing an insect species, there is a relationship between the quality and quantity of food offered and their larval growth rate ( Grandison et al 2009 , Borzoui et al 2018 , Suits et al 2017 ). Moreover, larval diet has a considerable impact on adult fecundity and egg fertility ( Zhang et al 2011 , Majd-Marani et al 2017 ). Eating a low-quality food has been associated with high mortality, reduced growth, delayed development, and low reproductive output in insect herbivores ( Awmack and Leather 2002 , Behmer 2006 , Suits et al 2017 ).…”
mentioning
confidence: 99%
“…It has previously been suggested that an integrated pest management strategy to protect grains in storage systems could be performed utilizing resistant cultivars ( Rossa et al 2013 , Hosseininejad and Naseri 2015 , Golizadeh and Abedi 2017 , Majd-Marani et al 2017 ). However, there is a little published information that has examined the management of R. dominica by resistant cultivars.…”
mentioning
confidence: 99%
“…The recorded values of the intrinsic and finite rate of increase were lower than the corresponding ones of other stored-product insects, indicating that T. castaneum had a lower population increase potential even on semolina. For example, the khapra beetle, Trogoderma granarium Everts (Coleoptera: Dermestidae) exhibited 2.50-4.21, 2.79-5.51 or 3.36-4.71 times higher values of intrinsic rate of increase and 1.02-1.05, 1.03-1.07 or 1.04-1.05 when fed on different varieties of barley, hybrids of maize or grain commodities, respectively [16,40,41]. Rahimi Namin et al [33] reported shorter durations of development of larvae, shorter longevities of female or male adults and higher values of the intrinsic or finite rate of increase when T. castaneum fed on different varieties of barley than the observed corresponding values of the current study on semolina.…”
Section: Discussionmentioning
confidence: 99%